2000
DOI: 10.1007/bf02780526
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical investigatigation of migration inhibitory factor-related protein (MRP)-14 expression in hepatocellular carcinoma

Abstract: Migration inhibitory factor-related protein (MRP)-8 and -14 belong to the S-100 protein family and are associated with myeloid cell differentiation. MRP is also expressed in some epithelia. However, there are few reports for the investigation on carcinomas. Using the monoclonal antibody 60B8 against MRP-14, we carried out the immunohistochemical evalution of MRP-14 expression in 70 cases of hepatocellular carcinoma (HCC), and examined the relation to tumor differentiation and vascular invasion. Positively stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 19 publications
9
25
0
Order By: Relevance
“…Among S100 proteins, S100A4, S100A8, and S100A9 have emerged as potential prognostic markers for poor patient survival and metastasis of a number of cancers (14,(23)(24)(25). S100A8 and S100A9 were shown to be overexpressed in gastric cancer (26,27), prostate cancer (28), breast cancer (29), lung adenocarcinomas (30), pulmonary adenocarcinoma (30), and hepatocellular carcinoma (31). Consistent with the present study, we previously showed that S100A8 and S100A9 play critical roles in the invasive phenotype of a human gastric cancer cell line, SNU484 (27).…”
Section: Discussionsupporting
confidence: 90%
“…Among S100 proteins, S100A4, S100A8, and S100A9 have emerged as potential prognostic markers for poor patient survival and metastasis of a number of cancers (14,(23)(24)(25). S100A8 and S100A9 were shown to be overexpressed in gastric cancer (26,27), prostate cancer (28), breast cancer (29), lung adenocarcinomas (30), pulmonary adenocarcinoma (30), and hepatocellular carcinoma (31). Consistent with the present study, we previously showed that S100A8 and S100A9 play critical roles in the invasive phenotype of a human gastric cancer cell line, SNU484 (27).…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that MRP14 expression level has a positive correlation with the differentiation degree of carcinomas derived from glandular cells, such as hepatocellular carcinoma, cholangiocellular carcinoma and pulmonary adenocarcinoma. In poorly differentiated adenocarcinoma (AC) cases, immunoreactivity of MRP8 and MRP14 was significantly higher than that in the moderately and well differentiated AC cases [24,26] . These differences might reflect the different pathways or mechanisms that MRP8 and MRP14 were involved in tumorigenesis of different cell origin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have subsequently shown that the deregulation of MRP8 and/or MRP14 was associated with several common human malignancies, including carcinomas of the skin, stomach, colon, nasopharynx, lung, liver and anus, and follicular lymphoma as well [20][21][22][23][24][25][26][27][28] . Therefore, our results further suggest that reduced expression of MRP8 and MRP14 in ESCC cells, but not in normal cells, plays an important role in esophageal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100A8/A9 are elevated in inflammatory diseases, such as rheumatoid arthritis, cystic fibrosis, and inflammatory bowel disease (23)(24)(25). In addition, they are upregulated in cancers, such as hepatocellular carcinoma (26), breast cancer (27), ovarian cancer (28), and gastric cancer (GC) (29). S100A8/A9 mediates their effects by binding to cell surface receptors, such as heparan sulfate (30), TLR4 (31), and carboxylated N-glycans expressed on RAGE (32,33), on immune cells and tumor cells.…”
mentioning
confidence: 99%